My best choice after a round trip from illness - Tommasi, Chiara; Pellegrino, Benedetta; Quaini, Federico; Musolino, Antonino (Acta Biomedica Atenei Parmensis, 2017)
This article reports the experience of a 24-years-old Medical Student who was diagnosed a “Hodgkin Lymphoma” during her last year at the University Medical School of Parma (Italy) and her difficult choice to try to become an Oncologist.